Compliance optimization of the truss structures - Czarnecki, Sławomir (Computer Assisted Methods in Engineering and Science, 2023)
The paper discusses the problem of designing the stiffest truss with a given and fixed number of joints and element connections. The design variables are the cross sectional areas of the bars or/and the nodal points locations. In each case a maximal volume of a truss, constituting an isoperimetric unilateral condition is prescribed. The nodal force vector is assumed to be independent of the design variables, hence fixed during the optimization process. The equilibrium problems of the trusses are modeled by the conventional linear as well as nonlinear finite element analyses taking into account large nodal displacements and small deformations of members. New optimal layouts of plane and space trusses are presented. These new layouts are found by using the moving asymptotes algorithm, the simplex method and the optimality criteria method.